2000
DOI: 10.1200/jco.2000.18.23.3964
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Study in Advanced Cancer Patients of a Diversified Prime-and-Boost Vaccination Protocol Using Recombinant Vaccinia Virus and Recombinant Nonreplicating Avipox Virus to Elicit Anti–Carcinoembryonic Antigen Immune Responses

Abstract: rV-CEA was more effective in its role as a primer of the immune system; avipox-CEA could be given up to eight times with continued increases in CEA T-cell precursors. Future trials should use rV-CEA first followed by avipox-CEA. Vaccines specific to CEA are able to generate CEA-specific T-cell responses in patients without significant toxicity. T-cell responses using vaccines alone may be inadequate to generate significant anticancer objective responses in patients with advanced disease. Cytokines such as GM-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
128
0
7

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 311 publications
(137 citation statements)
references
References 20 publications
2
128
0
7
Order By: Relevance
“…Further increases in CEA-specific T-cell precursors were seen when local granulocyte-macrophage colony-stimulating factor (GM-CSF) and low-dose interleukin (IL)-2 were given with subsequent vaccinations. 117 Direct transfer of cytokine genes to tumor cells has emerged as a third immunotherapeutic tool in oncolytic virotherapy to increase its antitumor efficacy. The rationale behind this approach is that expression of cytokine genes in tumor cells, delivered by oncotropic viruses, will stimulate inflammatory and immune responses against these cells, thereby enhancing the antitumor effects of oncolytic viruses.…”
Section: Enhancement Of Viral Intrinsic Antitumor Potencymentioning
confidence: 99%
“…Further increases in CEA-specific T-cell precursors were seen when local granulocyte-macrophage colony-stimulating factor (GM-CSF) and low-dose interleukin (IL)-2 were given with subsequent vaccinations. 117 Direct transfer of cytokine genes to tumor cells has emerged as a third immunotherapeutic tool in oncolytic virotherapy to increase its antitumor efficacy. The rationale behind this approach is that expression of cytokine genes in tumor cells, delivered by oncotropic viruses, will stimulate inflammatory and immune responses against these cells, thereby enhancing the antitumor effects of oncolytic viruses.…”
Section: Enhancement Of Viral Intrinsic Antitumor Potencymentioning
confidence: 99%
“…Furthermore, it has been shown that T cells stimulated to recognize PSA can specifically kill PSA-expressing tumor cells (9,10) and that these PSA-based vaccines are well tolerated with no doselimiting toxicities noted (12 -14). It has also been shown in both preclinical studies (15) and clinical studies (16,17) that a primary vaccination with rV followed by multiple boosting vaccinations with recombinant avipox vaccine is superior to the reciprocal regimen or the continued use of one vaccine.…”
mentioning
confidence: 99%
“…An ongoing clinical trial is using rV-PSA prime vaccination followed by multiple avipox-PSA boosts. In a phase I clinical trial, Marshall et al showed that rV-CEA followed by multiple avipox-CEA inoculations (VAAA strategy) in randomized patients was significantly more potent in inducing CEA-specific Tcell precursor frequency than the converse AAAV treatment [21]. In addition, this difference appeared to be clinically relevant, as there was a statistically significant increase in survival in the VAAA arm (P ¼ 0.0018).…”
Section: Discussionmentioning
confidence: 95%